Literacy: Issues of culture, gender, and hidden curriculum - David F. Hemphill; Audrey K. Allen (Adult Education Research Conference, 1996)
Family literacy is a socially-contexted program delivery construct embraced with increasing fervor in recent years. Recent studies of family literacy programs for immigrant populations suggest that those who design and operate such programs must pay greater attention to hidden curriculum and social context issues including gender, culturally-mediated interpretations of the purposes of education, appropriate mother tongue usage, enhanced community participation, and more effective application of existing adult learning theory.